Lifestyle and Hedonic Shopping Motivation on Impulse Buying among ShopeePay Users on Shopee E-Commerce in North Banjarmasin - Dhiya Fairuz Adawiyah; Setio Utomo; Siti Rusidah; M. Hasanur Arifin (Journal of Business Transformation and Strategy, 2025)
This study aims to examine the partial and simultaneous effects of shopping lifestyle and hedonic shopping motivation on impulse buying among consumers who use ShopeePay as a payment method on the Shopee e-commerce platform in North Banjarmasin. A total of 100 respondents who had used ShopeePay and made at least one purchase on Shopee were selected using an accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that shopping lifestyle does not have a significant partial effect on impulse buying among ShopeePay users on Shopee in North Banjarmasin. In contrast, hedonic shopping motivation has a significant partial effect on impulse buying. Furthermore, shopping lifestyle and hedonic shopping motivation simultaneously have a significant effect on impulse buying among ShopeePay users on Shopee in North Banjarmasin